2016
DOI: 10.15408/ijee.v3i1.3619
|View full text |Cite
|
Sign up to set email alerts
|

EFL Student Teachers’ Speaking Anxiety: the Case in One English Teacher Education Program

Abstract: This present study examined student teachers’ Foreign Language Speaking Anxiety (FLSA) associated with gender and proficiency differences. The participants of the study were 72 second-year EFL student teachers at the English teacher education program of one public university in Jambi, Indonesia. A close-ended questionnaire developed from Syakur (1987) and Horwitz et al, (1986) was administered to the participants to explore their FLSA. The results indicated that EFL student teachers are highly anxious when spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
2
13
0
Order By: Relevance
“…In contrast to the present study, their studies found that the signs of anxiety that generally appeared in students' performances were slight and did not affect the performances. Other previous studies that also reported contradictory results are from Agudo (2013), Abrar et al (2016), andRumiyati &Setfika (2018). By having an opposite result to the present study, their studies are in agreement that the average level of speaking anxiety is high, and they similarly share that the speaking anxiety signs that appeared were extremely debilitating to the students' performances.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast to the present study, their studies found that the signs of anxiety that generally appeared in students' performances were slight and did not affect the performances. Other previous studies that also reported contradictory results are from Agudo (2013), Abrar et al (2016), andRumiyati &Setfika (2018). By having an opposite result to the present study, their studies are in agreement that the average level of speaking anxiety is high, and they similarly share that the speaking anxiety signs that appeared were extremely debilitating to the students' performances.…”
Section: Discussionmentioning
confidence: 91%
“…It seemed that our TEFL teacher education program still fell short in raising the student-teachers' confidence for using the English language as many student-teachers' problems were related to their spoken language proficiency. Like many other EFL learners, Libyan student-teachers were hesitant to speak, unable to communicate or give presentations, lacked or misused vocabulary, demotivated by being forced to talk about uninteresting topics along with other negative factors that affected their spoken language proficiency (Abdallaha, 2018;Abrar, et al 2016;Dew, Kultsum & Armadi, 2017;Pathan, Aldersi, & Asout, 2014). If student-teachers who are being prepared to become teachers of the English language are having issues in their speaking skills, this is problematic.…”
Section: Research Problemmentioning
confidence: 99%
“…In the area of teaching English as a Foreign Language (TEFL), anxiety in foreignlanguagespeaking has caused great concern.Anxiety in foreign language speaking has been recognized as one of the important factors which affect students' learning process. A significant number of studies that concerns about this issue have been conducted since the 1970s (Abrar, Failasofah, Fajaryani, & Masbirorotni, 2016). Tanveer cited in Miskam and Saidalvi (2019) explains that EFL learners often express anxiety, nervousness, as well as stressfulnesswhile learning to communicate using English.…”
Section: Anxiety In Foreign Language Speaking and Its Levelsmentioning
confidence: 99%